2(3b-2)=3b+5

Simple and best practice solution for 2(3b-2)=3b+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3b-2)=3b+5 equation:


Simplifying
2(3b + -2) = 3b + 5

Reorder the terms:
2(-2 + 3b) = 3b + 5
(-2 * 2 + 3b * 2) = 3b + 5
(-4 + 6b) = 3b + 5

Reorder the terms:
-4 + 6b = 5 + 3b

Solving
-4 + 6b = 5 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
-4 + 6b + -3b = 5 + 3b + -3b

Combine like terms: 6b + -3b = 3b
-4 + 3b = 5 + 3b + -3b

Combine like terms: 3b + -3b = 0
-4 + 3b = 5 + 0
-4 + 3b = 5

Add '4' to each side of the equation.
-4 + 4 + 3b = 5 + 4

Combine like terms: -4 + 4 = 0
0 + 3b = 5 + 4
3b = 5 + 4

Combine like terms: 5 + 4 = 9
3b = 9

Divide each side by '3'.
b = 3

Simplifying
b = 3

See similar equations:

| -s^2+4s-6=0 | | 11-4a=4 | | 8y+9=10+8y | | 14+3n=8n-3n-12 | | 5-2y+3+4y=8 | | -5(x+2)+8x=-2+3x-8 | | 9x-139=3x-13 | | -6(2+x)=4-8x | | (4x)=(x+120) | | 3(2x-7)-7(x-8)=x-7-6+4x | | (1+c^2)(4c^2+7c-3)=0 | | 15-(-4)=x | | 6(2x-9)=4+11x | | 18/7.5=x/5 | | 3x-y+z=1 | | -3x-5=6x-32 | | 13=2y-3y+4 | | 5x^2-10x-80=0 | | 2(w-3)=3(w-1) | | 7k^2-6k*3=3 | | 32/4=b+4/3 | | 80+6x=145+7x | | 8=8n-4(a+8) | | .125d+7=16 | | 16a^2+24a+9= | | 2x-3y+z=-3 | | -3x^2+11x+25=0 | | 2x-1+6x=28 | | y=2x(4+3)-2 | | -11+z=6(z-4) | | 9v^2-121f^2= | | -7-2x-x=2 |

Equations solver categories